Strategien einer Übersetzungsdidaktik - Kardic, Mira (Glottodidactica, 2006)
The present article is devoted to discussing and carrying out translation methodology classes on German, Bosnian, Croatian and Serbian. The author assumes that not only the classes but also their planning itself should be perceived as a process.